(untitled) (Journal of Pakistan Orthopaedic Association, 2023)
Objectives: To evaluate the association between excessive stairs use and severity of osteoarthritis in Pakistani population. Methods: A Observational Cross sectional study was conducted at the orthopaedics department, Jinnah Postgraduate Medical Centre, Karachi, Pakistan between May 2019 to September 2019 for a duration of five months. All patients who did not give consent, were younger than 18 years, had hormone replacement therapy, were diagnosed with hyperparathyroidism, aemochromatosis, or any other rheumatological disease, or had a history of major trauma or surgery or infection around the knee joint were excluded from the study. All data was analyzed using the statistical package for social sciences (SPSS version 26). Results: A total of 102 patients were enrolled in the study. The mean age of patients was 53.39 ± 3.96 years. Out of 102 patients 70.6% were male while 29.4% were female. The majority belonged to the group between the ages of 50 and 55 years. The mean body mass index was 28.67 ± 7.73 kg/m2. The majority of the patients with knee osteoarthritis belonged to unskilled group. The study found a significant relationship between excessive use of stairs and severity of osteoarthritis (p<0.001). The study shows that the greater the duration and number of stairs climbed, the more severe the osteoarthritis. Conclusion: The current study findings indicate that there is a significant relationship between excessive use of stairs and severity of osteoarthritis. Further large scale, longitudinal studies should be conducted to explore the risk factors associated with knee osteoarthritis and patient outcomes.